ISLAMIC RELIGIOUS EDUCATION BASED ON BOARDING SCHOOL OF MTS AL-FATAH TEGALWARU - Imam Tabroni; Dina Fatimah; M. Fahmi Hidayat; Siti Nurul H (Education : Jurnal Sosial Humaniora dan Pendidikan, 2022)
Boarding schools are an example of Islamic education that combines two social systems, namely Islamic boarding schools and school institutions. Islamic boarding schools and school education have their own social systems and priorities. Boarding school aim to create human resources who have faith and piety as well as fully master science and technology. Education is structured as well as possible so that students are able to understand and live the values taught in an education. For this reason, Islamic religious education must be able to build the character of students better, reflecting an Islamic character that upholds moral values, tolerance, social integrity and responsibility. Many of the problems that arise in this country, among others, are caused by the depletion of moral values. Therefore, ensuring that society adheres to these values is not an easy task, but it needs to be done. Without understanding these values, it is impossible for someone to practice them in life. It is known that the most effective method is through education. Therefore, the purpose of this study was to find out how Islamic religious education in boarding school, namely in Mts-Alfatah